2020
DOI: 10.21203/rs.3.rs-17570/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnaporthe oryzae Systemic Defense Trigger 1 (MoSDT1)-Mediated Metabolites Regulate Defense Response in Rice

Abstract: Background: Some of the pathogenic effector proteins play an active role in stimulating the plant defense system to strengthen plant resistance. Results: In this study, ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOF-MS) was implemented to identify altered metabolites in transgenic rice containing over-expressed M. oryzae Systemic Defense Trigger 1 (MoSDT1) that was infected at three-time points. The characterized dominating metabolites were organic acids a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In plants, single metabolic markers have been suggested to assess the stress intensity, e.g., proline, which accumulates drought stress-prone plant species (Hayat et al 2012). Later, metabolic variables were found to be useful markers to detect stress damage or resistance and hence the diagnostic markers have been developed in the form of enzymes (Gibon et al 2004), metabolites (Korn et al 2010;Duan et al 2021), transcripts (Tamaoki et al 2013) and amino acids (Zhao et al 2021).…”
Section: Transcription Factors and Regulatory Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, single metabolic markers have been suggested to assess the stress intensity, e.g., proline, which accumulates drought stress-prone plant species (Hayat et al 2012). Later, metabolic variables were found to be useful markers to detect stress damage or resistance and hence the diagnostic markers have been developed in the form of enzymes (Gibon et al 2004), metabolites (Korn et al 2010;Duan et al 2021), transcripts (Tamaoki et al 2013) and amino acids (Zhao et al 2021).…”
Section: Transcription Factors and Regulatory Elementsmentioning
confidence: 99%
“…Lately, Zhao et al (2021) identified proline and alanine as important metabolic markers for head blight resistance in wheat. In a recent study by Duan et al (2021), metabolites namely shikimate, galactinol, trehalose, D-mannose, linolenic acid, dopamine, tyramine, and L-glutamine were identified as metabolic markers imparting plant defense response against rice blast. The list of different plant metabolic markers identified to provide resistance against the diseases has been given in Table 4.…”
Section: Transcription Factors and Regulatory Elementsmentioning
confidence: 99%
“…Our result showed that the terms “Sphingolipid metabolism”, “Plant‐pathogen interaction” and “Biotin metabolism” were found to be enriched (Figure S6). Both sphingolipids and biotin played a predominant role in plant defence, especially in disease resistance (Duan et al, 2021; Yanagawa et al, 2017).…”
Section: Resultsmentioning
confidence: 99%